IDEAL FORMULATION OF DIVERSION IN LAW ENFORCEMENT OF CHILDREN IN THE FUTURE - Siregar, Gomgom TP (Jurnal Pembaharuan Hukum, 2022)
The purpose of this writing is to find out and analyze the formulation of law enforcement for children in the future so that the punishment of children is more useful, the approach method uses a normative juridical approach, the results of the study state that the implementation of diversion in article 7 paragraph (2) letter a SPPA Law carries a prison sentence under 7 years to get diversion so that the limitation on the implementation of diversion in Article 7 paragraph (2) letter a will have an impact on the child's right to get diversion when the child commits a crime above the threat of imprisonment for 7 years and above which should be the problem can be resolved peacefully based on the purpose of diversion but there is restrictions on the threat of imprisonment under 7 years in the implementation of diversion. The general principles contained in the Convention on the Rights of the Child should be taken into consideration to amend or remove conditional restrictions on diversion for imprisonment under 7 years because they have deviated from the essence of children's rights and the general principles contained in the Convention on the Rights of the Child.